2014
DOI: 10.1111/epi.12600
|View full text |Cite
|
Sign up to set email alerts
|

Changes in glutamate concentration, glucose metabolism, and cerebral blood flow during focal brain cooling of the epileptogenic cortex in humans

Abstract: SUMMARYObjective: Recently, focal brain cooling (FBC) was proposed as a method for treating refractory epilepsy. However, the precise influence of cooling on the molecular basis of epilepsy has not been elucidated. Thus the aim of this study was to assess the effect of FBC on glutamate (Glu) concentration, cerebral blood flow (CBF), and glucose metabolism in patients with intractable epilepsy. Methods: Nine patients underwent FBC at 15°C for 30 min prior to cortical resection (n = 6) or hippocampectomy (n = 3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 32 publications
2
35
2
1
Order By: Relevance
“…It has long before suggested that neurotransmitter release has temperature dependence which causes changes in PSP generation [ 61 ]. This was confirmed by experimental observations of reduced efficacy of neurotransmitter vesicle release and reduced extracellular glutamate concentration during cooling [ 38 , 40 ] that imply lower neurotransmitter concentration at the synapses to bind at the post-synaptic receptor and generate PSP. In light of this, it was straightforward to assume a temperature dependence on the post-synaptic impulse response function in a neural mass model.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…It has long before suggested that neurotransmitter release has temperature dependence which causes changes in PSP generation [ 61 ]. This was confirmed by experimental observations of reduced efficacy of neurotransmitter vesicle release and reduced extracellular glutamate concentration during cooling [ 38 , 40 ] that imply lower neurotransmitter concentration at the synapses to bind at the post-synaptic receptor and generate PSP. In light of this, it was straightforward to assume a temperature dependence on the post-synaptic impulse response function in a neural mass model.…”
Section: Discussionsupporting
confidence: 66%
“…We explore prospective mechanisms of cooling on epileptic discharges by introducing temperature dependence in the neural mass model of Wendling et al in light of findings observed in in vitro and in vivo experiments published in literature. In particular, changes in synaptic dynamics were reported from in vitro cooling experiments such as reduction in the efficacy of neurotransmitter vesicle release [ 38 ], loss of dendritic spines [ 39 ] and reduced glutamate concentrations [ 40 , 41 ], suggesting a possible synaptic mechanism. A recent study with patients with intractable epilepsy also reports reduced extracellular glutamate and GABA concentrations during focal brain cooling [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the use of Peltier device may be more feasible in anesthetized patients during the acute phase of cerebral ischemia in anesthetized patients. The Peltier cooling system has been extensively studied for the treatment of epilepsy and has demonstrated clinical efficacy with an intraoperative application in epilepsy patients (Nomura et al, 2014). Efforts to develop clinically feasible implantable device are continuing (Dinis et al, 2017;Hata et al, 2017), and Peltier's elementbased cooling has been successfully tested in nonhuman primate (Inoue et al, 2017), as a potential clinically therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Its utility and safety to control cortical excitation has been reported both from experimental animal 11,14,15 and human research 10,16 . A common form of CC clinical utilization is topical application of cooled saline during events of epileptiform discharges and seizures during neurosurgeries [17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%